Professoras alfabetizadoras e o ensino fundamental de nove anos: concepções frente à infância e à ludicidade - Vargas, Jamily Charão (2010)
This post-graduation study is linked to the LP1 research area, called Teacher Training and Professional Development, of Education Post-Graduation Program from Universidade Federal de Santa Maria. It focus is in three teachers life history, aiming to study the childhood and ludic activities conceptions, during the personal and professional life trajectory of the teachers, with the basic education enlargement. A qualitative approach is used, with the Case Study Method of the type Histories of Life, tends as instruments of collection of information the written autobiographies and the semi-structured interviews with the collaborators of the research. Starting from the reconstruction of their life histories, the three collaborators narrated their representations of childhoods and ludic activities, built in their personal and professional trajectory. It leans on in the studies of Priors (2007, 1995), Corazza (2000, 2002), Aries (2006), Negrine (2000), Fortune (2004), Kishimoto (2006, 2008), among others that approach the childhood and the ludic activities; in studies of Nóvoa (1992, 1995), Pereira (2000), Tardif (2000, 2002), Imbernón (2005), Sacristán (2006), among others that study the training teacher and teacher knowledge; as well as in the Laws, Opinions and Legal Orientations for the enlargement of the Basic Education. It is believed that the implementation of the Basic Education of nine years opens spaces for the discussion of the childhoods and of the ludic activities among the teachers, in search of solid practices for the new pointed perspectives for the didactic and pedagogic work with the six year-old children. It is considered the relevance of the Orientations and Reports of Ministry of Education (2004a, 2004b, 2006, 2007) to this work in the new first year of the Basic Education happens in a ludic perspective, approaching a literacy atmosphere and respecting the integral development of the childhood. In that sense, this research configures important moments of approach with the conceptions of childhood and ludic activities, pointing hypotheses for the construction of practices that it respect the childhood and value the ludic aspects inside of the classrooms of the first year of the Basic Education of nine-years-long.